THE EFFECT OF FEVER ON THE NERVOUS SYSTEM: PATHOPHYSIOLOGICAL MECHANISMS, CLINICAL MANIFESTATIONS, AND MODERN DIAGNOSTIC APPROACHES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article comprehensively analyzes the effects of fever on the central and peripheral nervous systems, emphasizing modern pathophysiological mechanisms, neuroinflammation, blood-brain barrier dysfunction, and neuronal metabolic disturbances. Based on current scientific evidence, the study evaluates neurological manifestations associated with fever, including febrile seizures, encephalopathy, cognitive impairment, autonomic dysfunction, and altered neurotransmitter activity. Furthermore, contemporary diagnostic methods, laboratory investigations, and neuroimaging approaches are discussed. Fever-induced neurological alterations remain a significant issue in clinical neurology and intensive care medicine. This article provides updated scientific information useful for medical students, neurologists, pathophysiologists, and clinical researchers.